2019
DOI: 10.29228/turkishstudies.22598
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenleri̇n İş Değerleri̇ İle Yaşam Boyu Öğrenme Eği̇li̇mleri̇ Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇

Abstract: This research was conducted to examine the relationship between teachers' work values and lifelong learning tendencies. Selected scales in terms of purpose; In the academic year 2016-2017 225 private teachers in the Üsküdar District of Istanbul were employed and 225 teachers were employed depending on the Ministry of National Education. In order to analyze the data, the dimension having the highest score according to the average of the work value dimensions given in the work result is the dimension "Achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Moreover, when the relevant literature is examined, it is seen that there is a very little research on high school students' or adolescents' lifelong learning tendencies (Asiloğulları, 2020;Brooks, 2006;Güzel, 2017;Kalçık, 2017;Semerci & Kalçık, 2017;Ünal & Kalçık, 2017). The studies conducted in the field of lifelong learning tendency were found to be largely focused on teachers (Gökyer, 2019;Tanatar & Alpaydın, 2019), pre-service teachers (İlic & Haseski, 2019;Yenice & Tunç, 2019), university students (Arslan et al, 2019;Denat et al, 2016) and trainees in different institutions (Adabaş, 2019;Akyol et al, 2018) while high school students or adolescents were not much preferred in these studies.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when the relevant literature is examined, it is seen that there is a very little research on high school students' or adolescents' lifelong learning tendencies (Asiloğulları, 2020;Brooks, 2006;Güzel, 2017;Kalçık, 2017;Semerci & Kalçık, 2017;Ünal & Kalçık, 2017). The studies conducted in the field of lifelong learning tendency were found to be largely focused on teachers (Gökyer, 2019;Tanatar & Alpaydın, 2019), pre-service teachers (İlic & Haseski, 2019;Yenice & Tunç, 2019), university students (Arslan et al, 2019;Denat et al, 2016) and trainees in different institutions (Adabaş, 2019;Akyol et al, 2018) while high school students or adolescents were not much preferred in these studies.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…When national (Adabaş, 2019;Akyol, Başaran, & Yeşilbaş, 2018) and international research (Castleberry, Ward, & Stein, 2019;Sullivan, Fulcher-Rood, Kruger, Sipley, & van-Putten, 2019) on lifelong learning are reviewed, it is seen that these studies largely focus on the investigation of lifelong learning skills in adults. There are many national studies investigating lifelong learning tendencies of university students (Arslan, Bıçakçıgil-Özsoy, & Aslan, 2019;Denat, Dikmen, Filiz, & Başaran, 2016;Yıldız-Durak & Sarıtepeci, 2019), teachers (Aydoğan, 2019;Gökyer, 2019;Tanatar & Alpaydın, 2019), pre-service teachers (Bulaç & Kurt, 2019;İlic & Haseski, 2019;Yenice & Tunç, 2019) and trainees in different institutions (Adabaş, 2019;Akyol et al, 2018). However, the number of studies conducted to determine young individuals' lifelong learning tendencies is very small in both national literature (Asiloğulları, 2020;Güzel, 2017) and international literature (Brooks, 2006).…”
Section: Research Problemmentioning
confidence: 99%
“…are effective factors in the formation of work values in organizations. There are studies in the literature that examine work values from various aspects (Tanatar & Alpaydın, 2019;Özcan, 2008;Altaş, 2019;Sığrı, 2007;Turan & Aktan, 2008;Yıldırım, 2009;Elizur & Sagie, 1999). These studies had a common point and reported that teachers' individual attitudes and professional values guide the formation of common principles and beliefs adopted at school through work values (Turan & Aktan, 2008;Bozkurt & Doğan, 2013;Altaş, 2019).…”
Section: Work Valuesmentioning
confidence: 99%
“…Alanyazındaki çalışmalar incelendiğinde, hayat boyu öğrenme konusunda farklı branşlarda görev yapan öğretmenlerle yürütülmüş birçok araştırma olmasına rağmen (Abbak, 2018;Akkaya-Tatlıdil, 2023;Ayaz, 2016;Aydın, 2020;Ayra, 2015;Buzkurt, 2021;Doğan, 2019;Gedik, 2019;Kabal, 2019;Kılıç, 2015;Lala, 2021;Özcan, 2011;Tanatar, 2017;Yaman, 2014), İngilizce öğretmenleri ile yürütülen çalışmaların sayısı oldukça azdır (Bekci, 2021;Ertaş, 2022;Selvi, 2011;Şen, 2021;Yenen, 2018). İngilizce dil öğretim sürecinde, hayat boyu öğrenme becerilerinin yansıtılmasına ilişkin İngilizce öğretmenlerinin görüşlerine odaklanan çalışmalara alanyazında rastlanılamamıştır.…”
Section: Introductionunclassified
“…İngilizce dil öğretim sürecinde, hayat boyu öğrenme becerilerinin yansıtılmasına ilişkin İngilizce öğretmenlerinin görüşlerine odaklanan çalışmalara alanyazında rastlanılamamıştır. Ayrıca, hayat boyu öğrenme odağında yürütülen çalışmalarda, çoğunlukla nicel araştırma yöntemleri ile öğretmenlerin hayat boyu öğrenme eğilimleri (Akpınar, 2020;Altın, 2018;Assadzadeh, 2019;Ayaz, 2016;Aydın, 2020;Ayra, 2015;Doğan, 2019;Gedik, 2019;Kabal, 2019;Kılıç, 2015;Korkmaz, 2019;Recepoğlu, 2021;Şahin vd., 2020;Şen, 2021;Tanatar, 2017;Taş, 2020;Yaman, 2014) ve hayat boyu öğrenmeye ilişkin yeterlik düzeylerinin (Abbak, 2018;Arslangilay, 2017;Bozat vd., 2014;Çalışkan-Toyoğlu & Doğan, 2020;Feng & Ha, 2016;Klug vd. 2014;Jovanova-Mitkovska & Hristovska, 2011;Özcan, 2011;Torun & Güvercin-Seçkin, 2021;Woonsun, 2014;Yıldırım, 2015;Yıldız-Durak & Tekin, 2020) incelendiği görülmektedir.…”
Section: Introductionunclassified